Genome-wide analysis suggests high level of microsynteny and purifying selection affect the evolution of EIN3/EIL family in Rosaceae - Cao, Yunpeng; Han, Yahui; Meng, Dandan; Li, Dahui; Jin, Qing; Lin, Yi; Cai, Yongping (PeerJ, 2017)
The ethylene-insensitive3/ethylene-insensitive3-like (EIN3/EIL) proteins are a type of nuclear-localized protein with DNA-binding activity in plants. Although the EIN3/EIL gene family has been studied in several plant species, little is known about comprehensive study of the EIN3/EIL gene family in Rosaceae. In this study, ten, five, four, and five EIN3/EIL genes were identified in the genomes of pear (Pyrus bretschneideri), mei (Prunus mume), peach (Prunus persica) and strawberry (Fragaria vesca), respectively. Twenty-eight chromosomal segments of EIL/EIN3 gene family were found in four Rosaceae species, and these segments could form seven orthologous or paralogous groups based on interspecies or intraspecies gene colinearity (microsynteny) analysis. Moreover, the highly conserved regions of microsynteny were found in four Rosaceae species. Subsequently it was found that both whole genome duplication and tandem duplication events significantly contributed to the EIL/EIN3 gene family expansion. Gene expression analysis of the EIL/EIN3 genes in the pear revealed subfunctionalization for several PbEIL genes derived from whole genome duplication. It is noteworthy that according to environmental selection pressure analysis, the strong purifying selection should dominate the maintenance of the EIL/EIN3 gene family in four Rosaceae species. These results provided useful information on Rosaceae EIL/EIN3 genes, as well as insights into the evolution of this gene family in four Rosaceae species. Furthermore, high level of microsynteny in the four Rosaceae plants suggested that a large-scale genome duplication event in the EIL/EIN3 gene family was predated to speciation.
Keywords: Rosaceae; EIN3/EIL; Microsynteny; Purifying selection; qRT-PCR